Development of pulse oximetry for application in medicine; Методология проектирования молодежного научно-инновационного пространства как основа подготовки современного инженера - Martemyanova N. I. (Integrity of traditions and innovations as the basis for the development of modern engineering science, 2014)
Заглавие с экрана